KMAS - IoT based - kindergarten monitoring and alerting system / Muhammad Haziq Naif Mohammad Nasir - Mohammad Nasir, Muhammad Haziq Naif (2018)
The market is flooded with many types of security systems for premises and businesses. However, current used kindergarten monitoring system has its own drawbacks because, it can be vulnerable and lack of other features. KMAS offers an effective kindergarten administration in monitoring and managing kindergarten operation. It is important to make sure that kindergarten are safe to live and leave by increase the monitorability of belongings and life of people thus being protected against danger, loss, and criminals. After doing research on past projects, the best model was identified. A new system built to eliminates the limitation of past projects. It able to detect LPG gas leak, water leakage, air temperature and humidity, intruder, and child entering prohibited areas. IoT seen as billions of smart, connected “things” a sort of universal global neural network in the cloud that will encompass every aspect of our lives, and its foundation is the intelligence that embedded processing provides. This project used IoT service from Blynk to push data to its server for database with the help of Arduino Mega 2560 embedded with Dragino Yun for Wi-Fi connectivity. Blynk application will be used to view sensor’s reading, show current system’s status and provide a little of kindergarten automation which is turning power fan and lights.